Dinamika Keagamaan Anak di Era Society 5.0: Strategi Penguatan Kurikulum Pendidikan Agama Islam Transformatif - Fitrohati, Rina; Mubin, Nurul; Roqib, Moh (IAIN Datuk Laksemana Bengkalis, Indonesia, 2025)
The dynamics of children's religiosity in the era of Society 5.0 and the challenges faced by the Islamic Religious Education (IRE) curriculum in responding to global changes and technological developments. Globalization and digitalization have influenced the understanding and practice of religion among the younger generation, marked by a shift in values and the emergence of hybrid spiritual identities. The IRE curriculum faces significant obstacles, such as low digital literacy among educators, infrastructure gaps, and a lack of contextual material. This study uses a library research method with a descriptive-critical approach to identify these challenges and offer strategic solutions. The results of the study show the importance of curriculum transformation through the integration of digital technology, strengthening teacher competencies, developing transformative learning models based on Islamic values, and instilling digital ethics and spirituality. Thus, the IRE curriculum is expected to produce a generation of Muslims who are adaptive, moderate, and moral in the midst of globalization and the digital era.